Effectiveness Of Colonoscopy And Fit In The Diagnosis Of Colon Adenocarcinoma In Uzbekistan (Texas Journal of Medical Science, 2026)
Colorectal cancer is a malignant tumor that develops in the colon or rectum, most often from benign polyps. It is one of the most common types of cancer and is successfully treated when detected early: the five-year survival rate in the early stages exceeds 90%. The aim of this study was to evaluate the effectiveness of FIT and colonoscopy in the diagnosis of colon adenocarcinoma in Uzbekistan. A prospective study was conducted involving 200 patients aged 40–75 years who were enrolled in a screening program. The sensitivity of FIT ranged from 80% to 91%, with specificity between 90% and 95%, while colonoscopy demonstrated a sensitivity of 88% to 98% and specificity of 92% to 99%. The detection rate of adenocarcinoma was 3.5%, while adenomas were identified in 18% of cases. The use of a sequential strategy (FIT → colonoscopy) increased the detection rate of early-stage cancer by 25-30%. The obtained results confirm the high effectiveness of combined screening and support its widespread implementation.